FACTORS INFLUENCING SAFETY PERFORMANCE OF BUMIPUTERA SMES IN MALAYSIA - W. Nurfahizul Ifwah W. Alias; Zulkifli Mohamed; Sakinah Mat Zin; Iskandar Hasan Tan Abdullah; Rosfatihah Che Mat (International Journal of Accounting, Finance and Business, 2022)
Small and medium enterprise (SME) plays an important role in the underpinning of a country’s economy. This study is aimed at getting a clearer view of the level of safety performance in various SME companies. The main concerns are the relative importance and need of different safety management practices and how they contribute to the overall safety performance of Bumiputera SMEs. The results deduced represent safety rules and procedures, safety communication, and entrepreneur commitment as the most important factors influencing safety performance. While safety promotion, worker involvement and safety training are not useful to the prediction of safety performance. Data was quantitatively collected through closeended questionnaires with a sample size of 272 Bumiputera SME entrepreneurs. Data was analysed through correlation and multiple regression using SPSS software. This paper presents a comprehensive diagnosis of safety performance indices of SME sector, the factors that reflect the insignificant relationship to safety performance suggestions to improve them. This enables practitioners and scholars to comprehend and make appropriate decisions that can enhance safety performance among Bumiputera SME entrepreneurs in Malaysia.